2000
DOI: 10.1094/phyto.2000.90.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Compatibility Groups of Verticillium dahliae in Israel: Their Distribution and Association with Pathogenicity

Abstract: A collection of 565 isolates of Verticillium dahliae, recovered between 1992 and 1997 from 13 host plant species and soil at 47 sites in Israel, was tested for vegetative compatibility using nitrate-nonutilizing (nit) mutants. Three vegetative compatibility groups (VCGs) were found and identified as VCG2A (28 isolates), VCG2B (158 isolates), and VCG4B (378 isolates) by using international reference strains. One isolate was heterokaryon self-incompatible. Of the VCG2B isolates, 92% were recovered from the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
113
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 22 publications
9
113
0
3
Order By: Relevance
“…Indeed, some studies point to a worldwide, prevalent distribution of VCG1, VCG2, and VCG4, suggesting a limited VCG diversity. Other investigations suggested that some VCGs may prevail on a crop in a given geographic area (Joaquim and Rowe 1991;Strausbaugh 1993;Katan 2000b;Subbarao et al 1995;Dobinson et al 1998;Elena 2000;Korolev et al 2000;Bhat et al 2003;Hiemstra and RatajGuranowska 2003). On the other hand, considering VCGs as fully genetically isolated groups may be a strict statement.…”
Section: Pathogenicity Groupsmentioning
confidence: 99%
“…Indeed, some studies point to a worldwide, prevalent distribution of VCG1, VCG2, and VCG4, suggesting a limited VCG diversity. Other investigations suggested that some VCGs may prevail on a crop in a given geographic area (Joaquim and Rowe 1991;Strausbaugh 1993;Katan 2000b;Subbarao et al 1995;Dobinson et al 1998;Elena 2000;Korolev et al 2000;Bhat et al 2003;Hiemstra and RatajGuranowska 2003). On the other hand, considering VCGs as fully genetically isolated groups may be a strict statement.…”
Section: Pathogenicity Groupsmentioning
confidence: 99%
“…In Spain, the D pathotype was first reported infecting cotton in a restricted area of intensive cultivation at the southern part of Andalusia in 1981 (2). This pathotype has now appeared to distant cotton-and olive-growing areas all over Andalusia (8), but has not yet been reported in other olive growing areas in northern Spain or other countries in the Mediterranean Basin, except Greece (11) and Israel (25).…”
Section: Additional Abstract: Olea Europaeamentioning
confidence: 99%
“…Nit mutants were generated on water agar-chlorate (WAC) (Korolev and Katan 1997) VCG3, strain 70-21; and VCG4A, strain 131 M) and Israeli nit testers (VCG2A, strain Cot200; VCG2B, strain Ep8M, and VCG4B, strain Pt15M) (Korolev et al 2000) in all possible combinations.…”
mentioning
confidence: 99%
“…Israeli nit testers of VCG2A, VCG2B, and VCG4B w e r e pr e v i o u s l y s h o w n to c o r r e l a t e w i t h t h e international OARDC reference strains (Korolev et al 2000;Korolev et al 2008;Rowe 1995). The cotton defoliating strain T9 (the original defoliating pathotype from cotton in California) belongs to subgroup VCG1A (Bell 1994).…”
mentioning
confidence: 99%